Development Of Arabic Teaching Materials For Integrated Islamic Kindergartens Al-Irsyad Dharmasraya - Riri Anggraini (Lisaanuna Ta`lim Al-Lughah Al-Arabiyah: Jurnal Pendidikan Bahasa Arab, 2022)
Education is a process of rebuilding experiences by which students acquire knowledge, skills, attitudes and values. In other words, it is the number of methods by which the elements of the environment around the learner are organized representing what is extended by the word environment in the sense of obtaining certain educational items. Teaching materials are one of the tools or teaching tools that contain materials, methods a`nd assessments that design educational materials to achieve educational goals. This research is a development research with 4D model which consists of four steps, namely; definition, design, development, and deployment. However, the researcher limits the development procedure in terms of assessing media based on experts in terms of teching material, design, language. The development procedure in this research is; the development needs analysis stage, namely the analysis of the needs of Arabic teachers, and student books. The results of the data obtained show a rating of